WUJUD KEBERAGAMAN RUANG ARSITEKTUR DI PESISIR SURABAYA (TINJAUAN RUANG PERTAHANAN DAN KETAHANAN) - Susanti, Wiwik Dwi; Safeyah, Muchlisiniyati; Mutia, Fairuz (Mintakat: Jurnal Arsitektur, 2022)
Pesisir Surabaya merupakan salah satu kawasan di Surabaya yang memiliki karakter ruang pertahanan dan ketahanan yang beragam. Wujud ruang arsitektur terbentang dari Utara sampai dengan Timur meliputi pertahanan teritori, sosial, budaya, alam dan arsitektur. Sedangkan ketahanan atau resilience lebih kepada proses mitigasi, adaptasi dan inovatif yang dilakukan oleh masyarakat. Pada sisi Utara meliputi kawasan Bulak, Perak dan Kedung Cowek terdapat pertahanan dari teritori, budaya dan sosial. Sedangkan kawasan Bulak ruang arsitektur lebih kepada ruang ketahanan yang telah mengalami proses adaptasi dan inovasi sehingga memiliki wujud yang beragam dipengaruhi oleh keberagaman etnis. Etnis Tionghoa, Arab dan Madura merupakan etnis yang berkembang di bagian pesisir tersebut, sehingga arsitektur yang berkembang juga beragam. Pada Pamurbaya bentuk ruang pertahanan berupa area konservasi mangrove yang bertujuan untuk melestarikan flora dan fauna asli hutan mangrove. Wujud ketahanan ruang berupa fasilitas wisata dengan mengusung konsep ekowisata. Penelitian ini menggunakan metode penelitian kualitatif deskriptif dengan menggunakan analisa kualitatif. Wujud keberagaman ruang arsitektur di pesisir Surabaya menjadi identitas kawasan, sehingga berdampak pada pemanfaatan ruang kota Surabaya.Coastal Surabaya is one of the areas in Surabaya that has various characters of defense and resilience. Its form includes two aspects, namely tangible and intangible. Tangible physical resilience is related to architecture while intangible resilience is related to cultural, social, etc. aspects (Hanan, 2014). Meanwhile, resilience is more about the mitigation, adaptation and innovative processes carried out by the community. The form of architectural space on the coast of Surabaya which stretches from North to East is very diverse including territorial defense, economy, social, culture, nature and architecture. On the north side covering the areas of Bulak, Perak and Kedung Cowek, there are territorial, cultural and social defenses. Meanwhile, in the Bulak area, the architectural space is more of a resilience space that has undergone a process of adaptation and innovation so that it has a variety of forms influenced by ethnic diversity. Ethnic Chinese, Arab and Madurese are ethnic groups that developed in this coastal area, so that the architecture that develops is also diverse. In Pamurbaya the form of defense space is in the form of a mangrove conservation area which aims to preserve the original flora and fauna of the mangrove forest. The form of spatial resilience in the form of tourist facilities by carrying the concept of ecotourism, due to the influence of the new tourism culture.This research uses descriptive qualitative research method using qualitative analysis. The form of the diversity of architectural spaces on the coast of Surabaya becomes the identity of the area, so that it has an impact on the use of Surabaya city space in the future.